OVERVIEW OF THE NUTRITIONAL STATUS OF TOODLER - Mustriwi Mustriwi; Dian Pitaloka Priasmoro; Ika Atifatus Sholiha (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
Nutritional problems are more susceptible to being experienced by children, especially toddlers. Nutritional disorders in toddlers (1-3 years) will affect the quality of life in the future. The purpose of this study was to describe the nutritional status of toddlers (1-3 years). The research design used a descriptive design. The population of this study was all toddler age children at Posyandu Duta Sehat 5 Ngawonggo Village, Tajinan District, a total of 30 toddler age children. Sampling used a total sampling of 30 children. This research was conducted on 1-3 April 2022. The research instrument used an observation sheet based on the results of anthropometric measurements of WAZ/HAZ. The results of the study found that the nutritional status of toddlers was mostly 66% with good nutritional status, a small portion of 20% with poor nutritional status, a small proportion of 7% with poor nutritional status and 7% overweight nutritional status. It is hoped that the mother of all toddlers more creative in choosing and preparing food ingredients for children under five so that nutritional problems do not occur at the age of toddlers.